Five Feet High and Rising : Cities and Flooding in the 21st Century - Jha, Abhas (2012)
Urban flooding is an increasingly important issue. Disaster statistics appear to show flood events are becoming more frequent, with medium-scale events increasing fastest. The impact of flooding is driven by a combination of natural and human-induced factors. As recent flood events in Pakistan, Brazil, Sri Lanka and Australia show, floods can occur in widespread locations and can sometimes overwhelm even the best prepared countries and cities. There are known and tested measures for urban flood risk management, typically classified as structural or engineered measures, and non-structural, management techniques. A combination of measures to form an integrated management approach is most likely to be successful in reducing flood risk. In the short term and for developing countries in particular, the factors affecting exposure and vulnerability are increasing at the fastest rate as urbanization puts more people and more assets at risk. In the longer term, however, climate scenarios are likely to be one of the most important drivers of future changes in flood risk. Due to the large uncertainties in projections of climate change, adaptation to the changing risk needs to be flexible to a wide range of future scenarios and to be able to cope with potentially large changes in sea level, rainfall intensity and snowmelt. Climate uncertainty and budgetary, institutional and practical constraints are likely to lead to a combining of structural and non-structural measures for urban flood risk management, and arguably, to a move away from what is sometimes an over-reliance on hard-engineered defenses and toward more adaptable and incremental non-structural solutions.